2023
DOI: 10.3390/v15051202
|View full text |Cite|
|
Sign up to set email alerts
|

Fungal Viruses Unveiled: A Comprehensive Review of Mycoviruses

Abstract: Mycoviruses (viruses of fungi) are ubiquitous throughout the fungal kingdom and are currently classified into 23 viral families and the genus botybirnavirus by the International Committee on the Taxonomy of Viruses (ICTV). The primary focus of mycoviral research has been on mycoviruses that infect plant pathogenic fungi, due to the ability of some to reduce the virulence of their host and thus act as potential biocontrol against these fungi. However, mycoviruses lack extracellular transmission mechanisms and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 438 publications
0
15
0
Order By: Relevance
“…Endornaviridae are ssRNA(+) viruses that do not have a true capsid as the genome is encapsulated together with a viral replicase and are able to infect plants and fungi. The genus Botybirnavirus (Orthornavirae) has fungi as natural hosts (Hough et al, 2023), however, we’ve found this RdRp in a holm oak tree sample, which could be indicative of some cross-kingdom capability.…”
Section: Discussionmentioning
confidence: 71%
“…Endornaviridae are ssRNA(+) viruses that do not have a true capsid as the genome is encapsulated together with a viral replicase and are able to infect plants and fungi. The genus Botybirnavirus (Orthornavirae) has fungi as natural hosts (Hough et al, 2023), however, we’ve found this RdRp in a holm oak tree sample, which could be indicative of some cross-kingdom capability.…”
Section: Discussionmentioning
confidence: 71%
“…Even if infrequent and inefficient, these cross-species transmission events contradict the dogma that mycoviruses are only transmitted horizontally between vegetatively compatible fungi through hyphal anastomosis. A few studies have been conducted to explore the factors involved in such vegetative compatibility-independent transmission (for review, see [ 23 , 77 ]). Some viruses appear to be able to weaken the vegetative incompatibility system, such as Sclerotinia sclerotiorum mycoreovirus 4, which downregulates the genes involved in nonself-recognition pathways, thus facilitating horizontal transmission of heterologous mycoviruses [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…HTS studies have shown mycoviruses to be widespread within the fungal kingdom. According to recent taxonomic advances, there are currently more than 250 recognized mycovirus species [ 22 , 23 ], and this number is rapidly growing. Most mycoviruses are positive-sense, single-stranded RNA (+ssRNA) or double-stranded RNA (dsRNA) viruses, although a few negative-sense single-stranded RNA (-ssRNA) and single-stranded DNA (ssDNA) viruses have also been described (for review, see [ 24 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Viruses that inhabit fungi, i.e. mycoviruses, are hosted by a wide range of fungal taxa (Hough et al 2023). The high phylogenetic diversity of mycoviruses is reflected by their current classification into 10 double-stranded (ds) RNA families, one unclassified dsRNA genus, 15 single-stranded (ss) RNA families and one ssDNA family (https://ictv.global/), and many novel taxa are awaiting description.…”
Section: Introductionmentioning
confidence: 99%